As contribuições do proformação/pedagogia/UERN para a melhoria da prática pedagógica de professores - Oliveira, Marcia Betania de (2010)
This dissertation aims at analyzing some relations established between teachers‟ formative proposal for docent knowledge and pedagogical practices in the Special Program of Professional Formation to Basic Education (Proformação in Portuguese) with the objective of investigating how teachers evaluate knowledge acquired during their course formation to identify its improvement in their pedagogical practice. This is a Pedagogical Program of the State University of Rio Grande do Norte chosen to be analyzed. The objective is to investigate how teachers, Proformação/Pedagogy course students evaluate privileged knowledge in that university formation and how the relation between this knowledge and their pedagogical practice are experienced in classroom as teachers, defining in which way knowledge constructed and reconstructed during the course contributes for an improvement of their pedagogical practices. We have interviewed fourteen Proformação/Pedagogy last-term teachers, emphasizing the analysis of their point of view as social actors related to docent university formation in service. The principles for this investigation comprehend a qualitative approach, in a case study modality, with an exploratory tendency, presented in the introductory section and along four chapters. The research is theoretically guided by Andoino (1998), Bardin (2009); Laville e Dione (1999); Bogdan and Biklen (1994), Hernandez Sampieri, Hernandez Collado and Baptista Lúcio (2006), among others. We justify this thematic choice, considering docent formation and its interface with an improvement for students‟ leaning, taking into account the strict relations between those elements. We have discussed on docent formative paradigms, based on a multireferential perspective, whose main authors that developed research in this area are: Gómez (1998), Sacristán e Gómez (1998), Tardif (2002), Altet (2001) Paquay e Wagner (2001), Garcia (1999), Baldi (2008), La Torre e Barrios (2002). We interviewed fourteen teachers, all of them in the last term of the Program. In the second chapter, we justify the choice of the subject, approaching docent formation and its relation with basic teaching. We understand that there is a strong relation between those aspects. In the third chapter, we discuss on some docent formative paradigms, among them, Gomes (1998), Sacristán and Gomez (1998), Tardig (2002), Altet (2001) Paquay and Wagner (2001), Garcia (1999), Baldi (2008), La Torre and Barrios (2002). We introduce the Pedagogical Program structure and specify which formative paradigms characterize it and identifying that one of the most prominent paradigm is a practical perspective with emphasis on reflexivity about the practice based on the premise that docent formation is be based on from learning to practice theory. We present an data analysis obtained from thematic categorization extracted subjects‟ discourses and, at the end, we discuss on evaluation of the teachers involved in the research related to the course contributions to provide an improvement for pedagogical practices developed by them inside their classrooms. We consider, thus, that teachers evaluate the Program as a guideline for (re)construction of diversified knowledge, which, in turn, provides the development of abilities to analyze classroom situations based on pedagogical theories and to develop investigative practice based on everyday experience. The results point out that some implications are relevant, among them: the thematic-choice, discussed previously, needs other kinds of investigations. The relation between theory and practice proposed in formation programs requires more systematic studies considering others aspects that characterize teaching process, and mainly, to provide investigative proposals of and about such practices